Analysis of the Influence of Self-Efficacy and Family Support on Entrepreneurial Intention - Marwan, Marwan; Soleman, Marwan Man; Safira Naser, Suliyanti Tsauri Ifat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The aim of this research is to explore the role of self-efficacy and family environment on entrepreneurial interest among students at the economics and business faculty at Khairun University. This research involved 100 students as samples that were sent questionnaire via Google Form. Data were analyzed using partial least squares (PLS). The research results succeeded in revealing that, variable family support and self-efficacy has a significant and positive effect on entrepreneurial intention. This shows that if the family support and self-efficacy variables of the students are good or high, it will cause the students' entrepreneurial intention to also be good or high. Likewise, vice versa; Self-efficacy can mediate the relationship between family support and entrepreneurship among students at the economics and business faculty at Khairun University. For this reason, in an effort to encourage interest businessman Students, apart from needing to improve family support, can also be done by increasing students' self-efficacy.